Advances in the study of oral microbiota and metabolism associated fatty liver disease: a systematic review - Huang, Mingming; Zhang, Xinbi; Zhou, Rui; Song, Yingzhe; Zhang, Jing (Frontiers in Cellular and Infection Microbiology, 2024)
ObjectiveThe oral microbiota is the second largest microbiota in the human body and has a significant impact on human health. Recent evidence suggests that dysbiosis of the oral microbiota may be associated with the development of metabolism-associated fatty liver disease (MAFLD). This review aimed to validate the relationship between oral microbial diversity and the development of MAFLD.MethodsA systematic evaluation was performed based on PRISMA guidelines. Three independent reviewers searched for relevant literature in several databases, including PubMed/Medline, Web of Science, and Scopus, with a search date ranging from the establishment of the databases to June 2024.ResultsA total of 1278 publications were initially screened, including five cross-sectional studies, seven case-control studies, one cohort study, and one retrospective study. These studies included a total of 3335 patients with MAFLD, 254 patients with MASH, and 105 patients with liver cirrhosis. All 14 included studies concluded that there was a correlation or potential correlation between oral microbiota and MAFLD. Seven studies found that the composition of the oral microbiota in MAFLD patients differed from that of healthy controls, and specific oral bacteria may be associated with an increased incidence of MAFLD. At the phylum level, several studies found differences in the abundance of the phyla Firmicutes, Proteobacteria, and Clostridia compared to healthy controls. Additionally, a study on oral fungi found significant differences in the phyla Proteobacteria and in the genus Staphylococcus between patients with MAFLD and healthy controls. At the genus level, Porphyromonas was studied most frequently, with all 8 studies identifying infection with Porphyromonas as a significant risk factor for pathological progression in MAFLD. Furthermore, a dysbiosis in the ratio of Porphyromonas gingivalis./Porphyromonas anomalies may be an important marker of MAFLD progression.ConclusionThere is an important association between the diversity of oral microbiota composition and MAFLD. This finding suggests the importance of oral health assessment and monitoring for the prevention or intervention of MAFLD.